ҚР азаматтық сот ісін жүргізу ерекшеліктерінің теориялық мəселелері (Journal of actual problems of jurisprudence, 2019)
In given article theoretical questions of features of civil legal proceedings which is discussed in a science of a civil proceduralright throughout all history of its development are considered. One authors try to give the developed substantial characteristic of civilprocess, to open structure of its basic components. Representatives of other point of view consistently defend idea of diffi cult structureof the civil process, based on the detailed analysis of character of communication between remedial activity and remedial relations incivil process.